2017
DOI: 10.1002/prot.25411
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear DEK interactome supports multi‐functionality

Abstract: DEK is an oncoprotein that is overexpressed in many forms of cancer and participates in numerous cellular pathways. Of these different pathways, relevant interacting partners and functions of DEK are well described in regard to the regulation of chromatin structure, epigenetic marks, and transcription. Most of this understanding was derived by investigating DNA-binding and chromatin processing capabilities of the oncoprotein. To facilitate the generation of mechanism-driven hypotheses regarding DEK activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…In support of its multifunctional roles, a recent study on the interactome of DEK in human cells identified hundreds of interactors, including chromatin remodeling, RNA processing, ribosome biogenesis, and stress response factors [118]. Gene ontology (GO) analysis further unveiled that proteins involved in translation were among the most frequent hits [118].…”
Section: The Dek Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of its multifunctional roles, a recent study on the interactome of DEK in human cells identified hundreds of interactors, including chromatin remodeling, RNA processing, ribosome biogenesis, and stress response factors [118]. Gene ontology (GO) analysis further unveiled that proteins involved in translation were among the most frequent hits [118].…”
Section: The Dek Proteinmentioning
confidence: 99%
“…In support of its multifunctional roles, a recent study on the interactome of DEK in human cells identified hundreds of interactors, including chromatin remodeling, RNA processing, ribosome biogenesis, and stress response factors [118]. Gene ontology (GO) analysis further unveiled that proteins involved in translation were among the most frequent hits [118]. In this context, it was previously shown that DEK-NUP214 activates the mTOR signaling pathway and the eukaryotic translation initiation factor 4E (EIF4E), which coincided with increased protein production [119,120].…”
Section: The Dek Proteinmentioning
confidence: 99%
“…DEK is considered a potential therapeutic target and a biomarker for breast and ovarian cancer [2325], retinoblastoma [26], colorectal [27] and bladder cancer [28] as well as for melanoma progression [29, 30]. DEK has a pleiotropic mode of action and can influence diverse regulatory circuits in the cell, a notion supported also by the recent elucidation of its interactome [31]. Downregulation of DEK expression increases the susceptibility to DNA damage [21, 32], attenuates apoptosis [33] and senescence [22], and affects proliferation and chemoresistance [24, 34, 35].…”
Section: Introductionmentioning
confidence: 99%
“…DDX21, also known as nucleolar RNA helicase II, is an ATP-independent helicase associated with many nuclear and nucleolar events, such as ribosomal RNA biogenesis [158] or unwinding of R-loops [159] and RNA guanine quadruplexes [160]. DDX21 also interacts with mitotic regulator PP1 [161] and oncoprotein DEK [162]. Additionally, upregulated DDX21 has been found to promote tumorigenesis in breast cancer by phosphorylating c-Jun, a component of AP-1 transcription factor involved in cell survival pathways [163].…”
Section: Ddx21mentioning
confidence: 99%